2021
DOI: 10.1002/cia2.12213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of delgocitinib 0.5% ointment on atopic dermatitis eczema intensity and skin barrier function

Abstract: Objectives Delgocitinib is a small‐molecule JAK inhibitor that has recently been approved in Japan as the world's first topical JAK/STAT pathway inhibitor for the treatment of atopic dermatitis (AD). In this study, the effects of delgocitinib 0.5% ointment treatment on skin rash severity and skin‐barrier function were examined. Methods Adult Japanese patients with mild‐moderate AD (n = 23) were recruited into the trial. Healthy subjects (n = 10) were examined in parallel. The effects of four weeks of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Abe et al 19 reported that delgocitinib was an effective topical option in treating AD; only after 2 weeks of treatment with delgocitinib 0.5% ointment, a statistically significant reduction in partial Eczema Area and Severity Index (pEASI) compared to baseline was observed. Such results persisted after 4 weeks of the trial and no evidence of skin inflammation was visible in clinical examination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abe et al 19 reported that delgocitinib was an effective topical option in treating AD; only after 2 weeks of treatment with delgocitinib 0.5% ointment, a statistically significant reduction in partial Eczema Area and Severity Index (pEASI) compared to baseline was observed. Such results persisted after 4 weeks of the trial and no evidence of skin inflammation was visible in clinical examination.…”
Section: Resultsmentioning
confidence: 99%
“…Mild and limited local adverse reactions were observed following the application of topical JAKi; application site erythema, itching, 19,25,32 eczema, 25 erysipelas, impetigo, dermatitis, 20,24,35 folliculitis, herpes simplex, 21 pain, hypoesthesia, 24 urticaria, first degree burn 32 and burning sensation. 22,36 Non-local adverse reactions were reported in few cases including nasopharyngitis, 22,23,25,36 decreased WBC and RBC count, 20,32 glucosuria, 20 increased alanine and aspartate aminotransferase and alteration of liver function tests, 32 transient increased platelet count, 29,31 hand-foot-and-mouth disease, 35 Kaposi varicelliform, 21,22,36 toothache, 25,32,38 backache, headache, 25,32,38 hyperkalaemia, limb abscess, restlessness, nausea, muscle strain, constipation, cough, allergic rhinitis, muscle strain, upper respiratory tract infection and bronchitis 25,32 and postinflammatory hyperpigmentation of the treatment site.…”
Section: Safety Of Topical Jak Inhibitorsmentioning
confidence: 99%
“…Also suggested was the possibility that topical medication is superior to systemic medication in terms of safety 21 . Tacrolimus hydrate ointment, delgocitinib ointment, and topical corticosteroid formulations are available to treat AD 22 . However, these topical agents are nonselective immunosuppressants associated with susceptibility to viral, bacterial, and fungal infections 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…21 Tacrolimus hydrate ointment, delgocitinib ointment, and topical corticosteroid formulations are available to treat AD. 22 However, these topical agents are nonselective immunosuppressants associated with susceptibility to viral, bacterial, and fungal infections. [22][23][24] In addition, skin atrophy and telangiectasia are common side effects of topical corticosteroid use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation